Adiposity Measures and Morning Serum Cortisol in African Americans: Jackson Heart Study. Issue 2 (24th January 2021) - Kluwe, Bjorn; Zhao, Songzhu; Kline, David; Ortiz, Robin; Brock, Guy; Echouffo‐Tcheugui, Justin B.; Sims, Mario; Kalyani, Rita R.; Golden, Sherita H.; Joseph, Joshua J.
Abstract : Objective: Altered hormonal regulation, including cortisol, is a proposed mechanism linking adiposity to obesity‐related disorders. We examined the association of anthropometric, adipokine, and body fat distribution measures of adiposity with morning serum cortisol in an African American (AA) cohort. Methods: We investigated the cross‐sectional associations of adiposity measures (BMI, waist circumference, leptin, adiponectin, leptin:adiponectin ratio, subcutaneous and visceral adipose tissue) and liver attenuation with cortisol in the Jackson Heart Study. Linear regression models were used to analyze the association between exposures and cortisol. Models were adjusted for multiple covariates. Results: Among 4, 211 participants, a 1‐SD higher BMI and waist circumference were associated with a 3.92% and 3.05% lower cortisol, respectively. A 1‐SD higher leptin and leptin:adiponectin ratio were associated with a 6.48% and 4.97% lower morning serum cortisol, respectively. A 1‐SD higher subcutaneous adipose tissue was associated with a 4.97% lower cortisol (all P  < 0.001). There were no associations of liver attenuation or visceral adipose tissue with cortisol. Conclusions: Several measures of adiposity are associated with lower morning serum cortisol among AAs, with leptin having the greatest magnitude. Future studies examining the role of morning serum cortisol in the pathway from adiposity to cardiometabolic disease in AAs are warranted.